Software‐based method for automated intraoperative planning of Schoettle Point in surgical medial patellofemoral ligament reconstruction: A comparative validation study - Privalov, Maxim; Kordon, Florian; Kunze, Holger; Beisemann, Nils; Vetter, Sven Yves; Franke, Jochen; Grützner, Paul Alfred; Swartman, Benedict (International Journal of Medical Robotics and Computer Assisted Surgery, 2024)
Background The aim of the study was to validate a software-based planning method for the Schoettle Point and to evaluate precision and time efficiency of its live overlay on the intraoperative X-ray. Methods A software-based method was compared with surgeons' manual planning in an inter- and intrarater study. Subsequently, K-wire placement was performed with and without an overlay of the planning. The time used and the precision achieved were statistically compared. Results The average deviation between the surgeons (1.68 mm; 2.26 mm) was greater than the discrepancy between the surgeons and the software-based planning (1.30 mm; 1.38 mm). In the intrarater comparison, software-based planning provided consistent results. Live overlay showed a significantly lower positioning error (0.9 ± 0.5 mm) compared with that without overlay (3.0 ± 1.4 mm, p = 0.000; 3.1 ± 1.4 mm, p = 0.001). Live overlay did not achieve a significant time gain (p = 0.393; p = 0.678). Conclusion The software-based planning and live overlay of the Schoettle Point improves surgical precision without negatively affecting time efficienc
Keywords: computer assisted surgery; intraoperative imaging; knee surgery; patellar dislocation